Evaluation of nasogastric tubes to enable differentiation between upper and lower gastrointestinal bleeding in unselected patients with melena. (February 2016) - Kessel, Boris; Olsha, Oded; Younis, Aurwa; Daskal, Yaakov; Granovsky, Emil; Alfici, Ricardo
Abstract : Gastrointestinal (GI) bleeding is a common surgical problem. The aim of this study was to evaluate how insertion of the nasogastric tube may enable differentiation between upper and lower GI bleeding in patients with melena. A retrospective study involving patients admitted to our surgery division with a melena was carried out between the years 2010 and 2012. A total of 386 patients were included in the study. Of these, 279 (72.2%) patients had negative nasogastric aspirate. The sensitivity of examination of nasogastric aspirate to establish the upper GI as the source of bleeding was only 28% and the negative predictive value of a negative nasogastric aspirate was less than 1%. Most patients who initially presented with melena and were found to have upper GI bleeding had a negative nasogastric aspirate. Insertion of a nasogastric tube does not affect the clinical decision to perform upper endoscopy and should not be routinely carried out.